A mission-embedded outreach program for NASA’s Multi-slit Solar Explorer (MUSE) mission: inspiring future generations of solar explorers beyond boundaries and backgrounds - Robinson, Rebecca A.; De Pontieu, Bart; Steel, Simon; Harman, Pamela; Polito, Vanessa; Jin, Meng (Frontiers in Astronomy and Space Sciences, 2025)
In the wake of the Decadal Survey for Solar and Space Physics, it is clear that the general knowledge of these subjects in the US is deficient in comparison to other subfields of astrophysics. This is concerning because we rely on the Sun to survive, and understanding our relationship with the Sun is crucial for understanding our immediate space environment. With that, it is our responsibility as scientists and educators to advocate for and share the knowledge of our Sun and space environments as accessibly as possible. One way to do so is by developing mission-specific outreach programs that tackle fundamental science questions and topics that are relevant to the Sun-Earth system. As a new and budding example, we introduce a mission-embedded outreach program for NASA’s Multi-slit Solar Explorer (MUSE) mission. This program officially began on 1 December 2024 and includes three main local partners: California Academy of Sciences, Chabot Space and Science Center, and the Boys and Girls Club of the Peninsula. Each partner’s scope of work is shaped by their resources and expertise, and each remains committed to creating reusable and versatile outreach products. This manuscript will summarize the scientific goals of the MUSE mission, detail the MUSE outreach program, highlight our collaborations with other heliophysics missions (e.g., PUNCH), and provide a preliminary assessment of our contribution to the future of heliophysics outreach.